Patterns and Challenges in Exotic Vegetables Marketing. Issue 4 (3rd July 2016) - Babalola, S. O.; Adeoye, I. B.; Adegbite, O. O.
ABSTRACT: How vegetables are handled after harvest may affect postharvest quality. Handling practices and challenges encountered in exotic vegetable marketing were evaluated. All marketers in the study area engaged in sales of carrots ( Daucus carota L.), sweet pepper ( Capsicum annuum L), cabbage ( Brassica oleracea L), cucumber ( Cucumis sativus L), and watermelon ( Citrullus lanatus . Thunb). Almost all sold potato ( Solanum tuberosum L), lettuce ( Lactuca sativa L.), yardlong bean ( Vigna unguiculata L.), and green bean ( Phaseolus vulgaris L) and only 4% sold radish ( Raphanus sativus L). Carrot, sweet pepper, and cucumber deteriorated within 4 days and lettuce deteriorated within 2 days. The most common packaging materials were polyethylene sacks; the major method of preservation used by marketers was keeping produce in baskets in airy rooms/well-ventilated stores. Problems encountered by marketers are postharvest loss (48%), inadequate storage facilities and transportation (20%), and low patronage (12%). Appropriate cooling and storage facilities during transportation and at wholesale and retail centers are needed.